Microlearning Media Development for Office Management: A TPACK-Based Analysis - Yuniarsih, Tjutju; Sobandi, A; Meilani, Rini Intansari; Indriarti, Resti (Journal Evaluation in Education (Online), 2025)
Purpose of the study: This study aims to analyze teachers’ proficiency in developing microlearning materials based on Technological Pedagogical Content Knowledge (TPaCK) to enhance students’ access to subject matter and improve the effectiveness and efficiency of learning outcomes. Methodology: This research employed a qualitative approach with a descriptive survey design. The study involved 37 teachers selected through purposive sampling, representing various educational levels and subject areas relevant to the integration of technology in teaching. Data were collected using structured interviews, questionnaires, and document analysis. The questionnaires, distributed via Google Forms, assessed teachers’ TPaCK proficiency across the domains of technology, pedagogy, and content knowledge in the design of microlearning materials. Interview data provided deeper insights into teachers’ practical experiences, while document analysis validated the quality of microlearning materials produced. Quantitative data from the questionnaires were analyzed using SPSS version 25 to obtain descriptive statistics, and qualitative data from interviews and document reviews were analyzed thematically to triangulate findings. Main Findings: The results revealed that most teachers demonstrated adequate proficiency in Technological Pedagogical Content Knowledge (TPaCK), particularly in integrating technology into instructional design. However, some teachers demonstrated limited mastery in applying pedagogical principles and in effectively using technology-based tools to develop microlearning materials. Novelty/Originality of this study: This study provides new insights into the relationship between TPaCK proficiency and the development of microlearning materials in blended learning environments. It underscores how teachers’ integrated competence in technology, pedagogy, and content directly influences the quality, accessibility, and effectiveness of digital instructional resources.